Correcting Students’ Understanding about Simple Direct Current (DC) Circuits through Scientific Approach - Susi Marcelina; Theo Jhoni Hartanto (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
This paper reports the effect of teaching electricity in simple DC circuits using a scientific approach on students’ understanding. The study was a pre-experimental design using 12 students. They were all studying in specific first secondary schools in the sub-urban area in Kasongan City, Katingan Regency, Central Kalimantan Province. This work used the multiple-choice tests to combine reasoning and certainty of response index (CRI). This test was used as pre and post-test, respectively, to assess students’ understanding of electricity in simple DC circuits. As a result, it is found that the secondary students have alternate conceptions about simple DC circuits, such as “electricity comes out of both ends of a cell” and “a circuit uses up the electric current”. On the other hand, the results of this study showed that the use of a scientific approach in learning could help students achieve conceptual change about electricity in simple DC circuits. The findings from the study suggested that there was a difference in students’ understanding of simple DC circuits between pre-test and post-test. The scientific approach to learning seemed to help students achieve conceptual change about electricity in simple DC circuits.